THE INHIBITORY EFFECT OF METAL OXIDE NANOPARTICLES AGAINST POULTRY PATHOGENS (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
The present study was aimed to investigate the antibacterial potential of metal oxide nanoparticles viz., Al2O3, Fe3O4, CeO2, ZrO2, and MgO against poultry pathogens viz., Klebsiella sp., E. coli, Staphylococcus sp. and Salmonella sp. The antibacterial activity of the metal oxide nanoparticles were assessed with well diffusion method. Various concentrations of nanoparticles were analyzed with minimum inhibitory concentration and minimum bactericidal concentration. Moreover, the potential nanoparticle was also tested with time kill assay. The ZrO2 showed maximum antibacterial activity against Salmonella sp. (15 ± 0.44 mm dia) followed by 12 ± 0.35 mm dia. against E. coli respectively. The MIC and MBC results revealed that, the ZrO2 nanoparticles inhibit the bacterial growth at a concentration of 2.5µg/ml against Salmonella sp. All the nanoparticles showed activity against all the tested pathogens. The time kill assay reveals that, the growth of the Salmonella sp. was inhibited by ZrO2 from the 1st h onwards. It is concluded from the present study that, the ZrO2 nanoparticles could be used as an effective antibacterial agent for the management of poultry systems.